2013
DOI: 10.1534/genetics.113.154856
|View full text |Cite
|
Sign up to set email alerts
|

Relating Phylogenetic Trees to Transmission Trees of Infectious Disease Outbreaks

Abstract: Transmission events are the fundamental building blocks of the dynamics of any infectious disease. Much about the epidemiology of a disease can be learned when these individual transmission events are known or can be estimated. Such estimations are difficult and generally feasible only when detailed epidemiological data are available. The genealogy estimated from genetic sequences of sampled pathogens is another rich source of information on transmission history. Optimal inference of transmission events calls … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
222
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(222 citation statements)
references
References 36 publications
0
222
0
Order By: Relevance
“…[117][118][119] These studies highlight important differences in the interpretation and characteristics of phylogenetic and transmission trees. For example, the timing of nodes (see Glossary) in the transmission tree corresponds to the point of transmission, whereas the timing of nodes in phylogenetic trees of genomic data reflect branching events (see Glossary) that may have taken place before transmission.…”
Section: Analysis Of the Spread Of Pathogens At Different Scales Realmentioning
confidence: 99%
See 2 more Smart Citations
“…[117][118][119] These studies highlight important differences in the interpretation and characteristics of phylogenetic and transmission trees. For example, the timing of nodes (see Glossary) in the transmission tree corresponds to the point of transmission, whereas the timing of nodes in phylogenetic trees of genomic data reflect branching events (see Glossary) that may have taken place before transmission.…”
Section: Analysis Of the Spread Of Pathogens At Different Scales Realmentioning
confidence: 99%
“…Hence, intra-host and inter-host evolution change the association between transmission and phylogenetic trees. 120 Although Bayesian methods have been developed that jointly estimate transmission and phylogenetic trees and capture within host pathogen dynamics, [117][118][119] in many cases there may be too much uncertainty to resolve person to person transmission networks, even with WGS data. new capacity to provide (near) real time data on the origin and transmission dynamics of pathogens could provide a major public health benefit.…”
Section: Analysis Of the Spread Of Pathogens At Different Scales Realmentioning
confidence: 99%
See 1 more Smart Citation
“…Leitner et al 1996], and is frequently used in practice [e.g. Stadler and Bonhoeffer 2013], the topologies of a viral phylogeny and transmission tree can differ significantly (Ypma, Marijn van Ballegooijen, and Wallinga 2013) due to within-host evolution and the sampling process (Giardina 2016). The ABC-SMC algorithm is computationally intensive, taking about a day when run on 20 cores in parallel with the settings we described in the methods.…”
Section: Modelling Assumptionsmentioning
confidence: 99%
“…However, these approaches, like the method developed by Jombart et al (2011), associated gene sequences with the host, rather than a bacterium infecting the host. Ypma, van Ballegooijen, and Wallinga (2013) showed that this assumption could lead to erroneous reconstruction of the transmission tree, and described a method for joint estimation of the phylogenetic tree of the infecting pathogen and the transmission tree of hosts to overcome this issue.…”
Section: Combining Genomic and Epidemiological Evidencementioning
confidence: 99%